Ferric iron in CaTiO₃ perovskite as an oxygen barometer for kimberlitic magmas : experimental calibration and applications - Bellis, Anthony (2005)
An oxygen barometer to estimate fO2 during the crystallization of kimberlites is developed using the Fe content of perovskite (Pv), a common groundmass phase in these rocks. With increasing fO2, more Fe exists in the kimberlitic liquid as Fe3+, and thus partitions into Pv, which accepts only Fe3+ into its crystal structure. Experiments to study the partitioning of Fe3+ between Pv and kimberlite liquid were conducted on simple and complex anhydrous kimberlite bulk compositions at 100 kPa over a range temperatures (1130 - 1300°C) and of fO2's from NN0+4 to NNO-5 (NNO, nickel-nickel oxide buffer) and at Nb and REE levels of 0 to 1.5 wt% and 1500 ppm respectively. For Nb-free experiments, the Fe2O3 content of Pv increases with fO2 according to the relation (at 2σ): Fe2O3 Pv (wt%) = 0.25 (0.04) ?NNO + 1.83(0.06) For experiments doped with Nb, two universal equations for the relationship between the Fe and Nb in Pv, and fO2 were defined. Based on a slope intercept fitting method (SIM) we obtain: Log Fe (0.04)=0.058(0.004)* ?NNO + 0.26(0.02)*Log Nb - 0.91(0.03) Based on a multiple linear regression method (MLR): Fe (0.031)= 0.404(0)* NNO + 0.50(0.021)*Nb + 0.030(0.001) with uncertainties at 2o, and Nb and Fe as cation units per 3 oxygens in both equations. Over the range of conditions of our experiments, these relationships show no temperature (T) dependence and are not affected by the bulk Fe content of the kimberlite starting material. The Fe2O3 content of Pv from natural kimberlites compiled from the literature corresponds to fO2 conditions of NNO-5 to NNO+1. Data on zoned Pv from a single kimberlite, the Phoenix pipe, suggests that cores record lower fO2 than rims, NNO-1 in = cores compared to NNO+1 in rims. Within the Somerset Island cluster, Pv from six pipes display an average relative f02 of NNO-4 to NNO+I . Within individual kimberlite pipes, however, the fO2 range recorded by Pv narrows to NNO-2.6 +/- 0.6 within the Nikos 1 pipe, and NNO +1- 2 within the Zulu pipe. Within the Lac de Gras cluster, Pv from ...